2018
DOI: 10.1139/cjps-2017-0338
|View full text |Cite
|
Sign up to set email alerts
|

Dry pea (Pisum sativum L.) protein, starch, and ash concentrations as affected by cultivar and environment

Abstract: Dry pea (Pisum sativum L.) is an important crop in the Northern Great Plains of the USA and Canada. Information on dry pea quality as affected by cultivars and environments is limited. This experiment determined the effects of dry pea cultivars and environments on protein, starch, and ash concentrations. Six dry pea cultivars (‘Arcadia’, ‘Bridger’, ‘CDC Striker’, ‘Cruiser’, ‘Montech 4152’, and ‘SW Midas’) were evaluated in a randomized complete block design with four replications in 22 environments. The result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 27 publications
6
16
0
Order By: Relevance
“…As our studies show, the main factor determining faba bean quality was the year of study. This finding is in line with other studies [48][49][50][51]. Some authors reported that water deficiency leads to an increased CP content in faba bean seeds [52,53].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…As our studies show, the main factor determining faba bean quality was the year of study. This finding is in line with other studies [48][49][50][51]. Some authors reported that water deficiency leads to an increased CP content in faba bean seeds [52,53].…”
Section: Discussionsupporting
confidence: 93%
“…A negative correlation was also observed between CP and SY. A negative relationship between SY and CP content was already described in earlier studies [38,51,52]. However, our studies also indicate that the determination coefficient R 2 value of the obtained dependencies relied on the time of harvest to a very small degree.…”
Section: Discussionsupporting
confidence: 82%
“…(2017) and Mohammed et al. (2018) reported protein contents of 15.9%–25.1% and 14.5%–27.8%, respectively. In both studies, growing environment was the major contributor to the variation in protein content.…”
Section: Protein Content Is Affected By Genetic and Environmental Factorsmentioning
confidence: 96%
“…Varietal differences can contribute to protein variability in pea (Hood‐Niefer et al., 2012; Mohammed et al., 2018; Wang et al., 2008). The varietal effect could be due to genetic mechanisms that directly affect proteins per se or genes that affect other traits that could contribute to protein variation indirectly (Ellis et al., 2011).…”
Section: Protein Content Is Affected By Genetic and Environmental Factorsmentioning
confidence: 99%
See 1 more Smart Citation